2022
DOI: 10.3390/foods11152377
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Physiological and Transcriptome Analysis Reveals the Mechanism for the Repair of Sub-Lethally Injured Escherichia coli O157:H7 Induced by High Hydrostatic Pressure

Abstract: The application of high hydrostatic pressure (HHP) technology in the food industry has generated potential safety hazards due to sub-lethally injured (SI) pathogenic bacteria in food products. To address these problems, this study explored the repair mechanisms of HHP-induced SI Escherichia coli O157:H7. First, the repair state of SI E. coli O157:H7 (400 MPa for 5 min) was identified, which was cultured for 2 h (37 °C) in a tryptose soya broth culture medium. We found that the intracellular protein content, ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…We previously reported the importance of cell damage causing growth delay for high-pressure inactivation of S. cerevisiae [ 24 ]. Hao et al demonstrated that the intracellular ATP concentration showed an upward trend after repairing Escherichia coli strain O157:H7 cells that were sub-lethally injured by HHP [ 25 ]. Our present results show that higher intracellular energy status resulted in increased piezotolerance of the S9arg parent strain as well as the UV1 mutant strain, which could be explained by the greater repairing ability of HHP-injured cells.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported the importance of cell damage causing growth delay for high-pressure inactivation of S. cerevisiae [ 24 ]. Hao et al demonstrated that the intracellular ATP concentration showed an upward trend after repairing Escherichia coli strain O157:H7 cells that were sub-lethally injured by HHP [ 25 ]. Our present results show that higher intracellular energy status resulted in increased piezotolerance of the S9arg parent strain as well as the UV1 mutant strain, which could be explained by the greater repairing ability of HHP-injured cells.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that RL exposure activated protein anabolism in E. coli O157:H7. Repairing damaged cell membranes is an energy-dependent process that requires RNA and protein synthesis; up-regulating the oxidative phosphorylation pathway provides ATP to support the repair process [ 53 , 54 ]. In summary, RL-induced membrane damage led to enhanced flux through energy metabolism and protein synthesis pathways to enable repair of the damage.…”
Section: Resultsmentioning
confidence: 99%
“…Peroxiredoxins have similar function as peroxidase, and in addition, participate in H 2 O 2 sensing and signaling, and maintaining peroxide level [ 30 ]. The participation of superoxide dismutase and catalase in bacterial coping with HHP stress has been reported in E. coli , Enterobacter sakazakii , yeast and deep-sea bacterium S. piezotolerans WP3 [ 22 , 31 , 32 , 33 ]. Yet, it is the first time that the involvement of peroxidase and peroxiredoxin in HHP adaptation was demonstrated.…”
Section: Discussionmentioning
confidence: 99%